Nghiên cứu tổng hợp hệ xúc tác TiO2-NiO/SiO2(Ia3d) dùng cho phản ứng oxi hóa hidrocacbon - Đức, Trương Đình; Dũng, Hà Tiến; Bằng, Nguyễn Văn; Thu, Hoa Hữu (Vietnam Journal of Chemistry, 2014)
Large-pore three-dimensional (3D) mesoporous silicas are among the most interesting mesoporous materials discovered in recent years, and they have attracted much attention for potential applications to make the supports for polyfunctional catalysts. In this report, the synthesis of the mesoporous silica with a bicontinuous cubic structure of Ia3d symmetry by using a commercially available triblock copolymer (EO20PO70EO20)–butanol mixture for the structure direction in aqueous solution was investigated. Then, cubic Ia3d mesoporous silica molecular sieves were modified with Ni-Ti mixed oxide and their structural characteristics were determined by X-ray diffraction, nitrogen physical sorption, TEM and their catalytic activity in gas phase oxidation reaction of LPG was studied.